Healthcare utilization and costs for patients initiating Dabigatran or Warfarin - Reynolds, Shannon L. (Health Qual Life Outcomes, 2017)
BACKGROUND: Novel oral anticoagulants (NOAC) such as dabigatran, when compared to warfarin, have been shown to potentially reduce the risk of stroke in patients with non-valvular atrial fibrillation (NVAF) together with lower healthcare resource utilization (HCRU) and similar total costs. This study expands on previous work by comparing HCRU and costs for patients newly diagnosed with NVAF and newly initiated on dabigatran or warfarin, and is the first study specifically in a Medicare population. METHODS: A retrospective matched-cohort study was conducted using data from administrative health care claims during the study period 01/01/2010–12/31/2012. Cox regression analyses were used to compare all-cause risk of first hospitalizations and emergency room (ER) visits. Medical, pharmacy, and total costs per-patient-per-month (PPPM) were compared between dabigatran and warfarin users. RESULTS: A total of 1110 patients initiated on dabigatran were propensity score-matched with corresponding patients initiated on warfarin. The mean number of hospitalizations (0.92 vs. 1.13, P = 0.012), ER visits (1.32 vs. 1.56, P < 0.01), office visits (21.43 vs. 29.41; P < 0.01), and outpatient visits (10.86 vs. 22.02; P < 0.01) were lower among dabigatran compared to warfarin users. Patients initiated on dabigatran had significantly lower risk of first all-cause ER visits [hazard ratio (HR): 0.84, 95% confidence interval (CI): 0.73–0.98] compared to those initiated on warfarin. Adjusted mean pharmacy costs PPPM were significantly greater for dabigatran users ($510 vs. $250, P < 0.001); however, mean medical costs PPPM ($1912 vs. $1956, P = 0.55) and mean total costs PPPM ($2381 vs. $2183, P = 0.10) were not significantly different compared to warfarin users. CONCLUSIONS: Dabigatran users had significantly lower HCRU compared to warfarin users. In addition, dabigatran users had lower risk of all-cause ER visits. Despite higher pharmacy costs, the two cohorts did not differ significantly in medical or total all-cause costs. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12955-017-0705-x) contains supplementary material, which is available to authorized users.